Electro-absorption and Electro-optic Characterization of L-Band InAs/InP Quantum-dash Waveguide - E. Alkhazraji; A. M. Ragheb; M. A. Esmail; Q. Tareq; H. Fathallah; S. A. Alshebeili; K. K. Qureshi; M. Z. M. Khan (IEEE Photonics Journal, 2020)
Electro-absorption and electro-optic characteristics of InAs/InP quantum-dash active region-based waveguide, emitting at ~1600 nm is investigated. Two major peaks were observed in the change of absorption spectrum with a maximum value of 7070 cm-1 at a bias voltage of -8V with an excellent uniform extinction ratio of ~15 dB across the wavelength range of operation (1460-1620 nm). The effect of temperature on electro-absorption (EA) measurement suggests a strong influence resulting in merging of two major change of absorption spectrum peaks with higher temperature. Furthermore, electro-optic measurements indicate a change in refractive index and its efficiency values of ~2.9 × 10-4 and ~0.5 × 10-4 V-1, respectively, hence exhibiting a low chirping factor of 0.9 and 1.5 at bias voltages of -2 V and -4 V, respectively. As a quasi-three-dimensionally confined structure possessing both quantum well- and quantum dot-like features, the quantum dash waveguide showed superior electro-absorption and electro-optic properties compared to quantum dots and close to that of quantum wells, while attaining low chirp and broad wavelength range of operation. This paves a way for potential realization of quantum dash-based EA and electro-optic modulator for future optical access networks, particularly operating in wide C- to L-band region.